Implementation information technology of competency assessment method of professional activity of the educational system employee - Kozlov, Valentyn; Kozlov, Yury; Moshchenko, Inna; Novykova, Olena (Національний технічний університет "Харківський політехнічний інститут", 2021)
Consistent and gradual spread in the West of the concept of "competence" in the practice of postgraduate education, professional development and retraining of professional personnel has led to the emergence in the education system of the concept of the so-called competency approach. Based on this concept, the International Labor Association introduces the concept of "key competencies", which include subject and social components, in the qualification requirements for professionals. The accumulated experience of implementing the competency approach in the education system has shown the presence of a number of problems due to the complexity of assessing the process and results of professional activities of educators. This problem has caused a flow of publications, varying in type, volume and content, from reputable and titular scholars to primary school teachers, the number of links to which there are millions on the Internet. The presence of many publications encourages the search for ways to solve the problem using the methods of qualimetry and information technology. In the article the information technology of the decision of problems of an assessment of professional activity of the educational system employee based on the competency approach is considered and offered for practical application. The essence of the method: a group of experts makes an information model (professiograms) of the educational system’ employee – lists (thesaurus and alphabetical index) of the evaluated features – the range of powers (competencies in the sense of professional capacity), as well as the set of knowledge, skills and personal characteristics (competencies in the sense of expertise); each assessment object the experts compare for each of the features and assign a point on a fourpoint scale of the order that characterizes the degree of compliance of the assessment object to a particular feature; the obtained sets of assessments (personograms) are processed accordingly; the processing result (ranked list) is submitted to the decision maker. As an example of application of the method, the procedure of assessment the professional activity of a group of beginning teachers of a higher education institution is considered.

Послідовне і поступове розповсюдження на Заході поняття “competence” у практиці післядипломного навчання, підвищення кваліфікації та перепідготовки кадрів професійної школи призвело до появи в системі освіти концепції так званого компетентнісного підходу. Спираючись на цю концепцію, Міжнародна асоціація праці вводить поняття “ключові компетенції”, що включають предметні й соціальні компоненти, у кваліфікаційні вимоги до спеціалістів. Накопичений досвід втілення компетентнісного підходу в системі освіти показав наявність низки проблем, обумовлених складністю оцінювання процесу і результату професійної діяльності спеціалістів-освітян.Ця проблема викликала потік публікацій, різних за видом, обсягом і змістом, за авторством від маститих і титулованих вчених до вчителів молодших класів середньої школи, кількість посилань на які в Інтернеті налічує мільйони. Наявність безлічі публікацій спонукає до пошуку шляхів вирішення проблеми з застосуванням методів кваліметрії та інформаційних технологій. У статті розглянуто і запропоновано до практичного застосування інформаційну технологію вирішення завдань оцінювання професійної діяльності працівника системи освіти, засновану на компетентнісному підході. Сутність методу: група експертів складає інформаційну модель (професіограму) працівника системи освіти –переліки (тезаурус і абетковий покажчик) оцінюваних ознак – кола повноважень (компетенції), а також знань, умінь та особистісних ознак (компетентності); кожен об’єкт оцінювання експерти порівнюють за кожною із ознак і приписують бал за чотирибальною шкалою порядку, що характеризує ступінь відповідності об’єкта оцінювання конкретній ознаці;отримані сукупності оцінок (персонограми) обробляють відповідним чином; результат оброблення (ранжируваний список) подається особі, що приймає рішення. В якості приклада застосування методу розглянуто процедуру оцінювання професійної діяльності групи викладачів-початківців закладу вищої освіти.
Інформаційна технологія реалізації компетентнісного методу оцінювання професійної діяльності працівника системи освіти
Keywords: competency; competence; expert method; decision making; компетентність; компетенція; експертний метод; прийняття рішень